SECURITIZATION OF COVID-19 AND STATE’S RESPONSE TO MITIGATE PANDEMIC THREAT - Iqbal Ramadhan (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Novel Coronavirus, commonly known as Covid-19, is a new type of viral species that has been discovered in China during November 2019. As of recent, Covid-19 has been a threat and a threat to the humans. Based on research performed by scientists, the coronavirus is a type of virus that can be transmitted to humans from wild animals. The first person infected with a virus is expected to appear in the city of Wuhan, China. Initially, Covid-19 was only endemic. Given the fact that so many people are infected with this virus, the WHO declared it a global pandemic. The Covid-19 phenomenon has gained prominence despite the danger that it presents to human life. The aim of this article is to analyze Covid-19 in the perspective of security studies. The author uses securitization concept to describe the Covid-19 phenomenon. The author used qualitative analysis methods. The author claims that the Covid-19 securitization process encourages state actors to define it as one of threat that needs to be overcame. Owing to variations in the securitization process between countries, the results are different among states. However, at one point, nation-state treated Covid-19 as a challenge to be solved. In the end, state actors need to strengthen their capabilities to stop the pandemic threat's pace.